THE LIBRARY AS SOCIAL AND CULTURAL INSTITUTION AND ITS EDUCATIONAL AND UPBRINGING MISSION - Матвійчук, О. Є. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to the libraries’ role and position in the modern society. We have found out and highlighted the notion “social and cultural Institution” and its partials. We have determinated functions of the social and cultural libraries work and its educational and upbringing mission.